1992
DOI: 10.1016/0014-4835(92)90087-9
|View full text |Cite
|
Sign up to set email alerts
|

CD68 antigen expression by human retinal pigment epithelial cells

Abstract: Although a primary role of the retinal pigment epithelium (RPE) is the phagocytosis of aged outer segment membranes, the RPE may also phagocytize particulates via several specific receptors that are characteristically present on mononuclear phagocytes of bone marrow origin. In recent immunophenotypic studies, CD68 monoclonal antibodies (mAb) have been shown to react selectively with a specific 110 kDa cytoplasmic glycoprotein present in mononuclear phagocytes from various sources. Designated as anti-macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
4
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
2
20
4
1
Order By: Relevance
“…Although hum an RPE cells may express mono nuclear phagocyte CD68 antigen (Elner et al, 1992) we found no reactivity of rat RPE to monoclonal antibodies of the ED series. EAPU includes the migration of EDI + macrophages and T cells through the Bruch's membrane-RPE layer.…”
Section: Immune Mechanismcontrasting
confidence: 66%
See 1 more Smart Citation
“…Although hum an RPE cells may express mono nuclear phagocyte CD68 antigen (Elner et al, 1992) we found no reactivity of rat RPE to monoclonal antibodies of the ED series. EAPU includes the migration of EDI + macrophages and T cells through the Bruch's membrane-RPE layer.…”
Section: Immune Mechanismcontrasting
confidence: 66%
“…Pleiotropic cytokines like IL-1/? and GM-CSF (Planck et al, 1993), IL-6 (Benson et al, 1992), and MCP (monocyte chemotactic protein) (Elner et al, 1991) evade from the RPE cell layer after receiving a signal (e.g. IL-1, or TNF-a) from the activated immune system which attracts or stimulates immunocompetent cells.…”
Section: The Rpe In Eapumentioning
confidence: 99%
“…In contrast to the pathologically transformed cells described above, these cells are involved in scavenging processes by phagocytosis of aged outer-segment membranes and share a panel of immunophenotypic antigen expression including HLA-DR, CD11c and CD14 with monocytes/macrophages. 29 The differentiation capacity of bone cells seems to have been underestimated in the past. Human bone-marrow fibroblasts have recently been shown to be able to differentiate into either adipocytes or osteogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cells possess macrophagelike properties, and have been shown to express hematopoietic cell markers in culture (Elner et al, 1992;Limb et al, 1997). Progressive retinal degeneration in Mitf vit/vit mutants is accompanied by a massive accumulation of 'macrophage-like' cells in the subretinal space between P21 and P60 (Boissy et al, 1987;Sidman et al, 1996), but it is not known if these cells are of monocyte-macrophage lineage, or alternatively, if they are RPE cells that have detached.…”
Section: Discussionmentioning
confidence: 99%